University Students, Faith, And Social Ethics: A Study Of The Level Religiosity In Higher Education (Jurnal Penelitian, 2025)
The increase in suicide, violence, and sexual harassment cases among university students reflects a psychological and moral crisis in higher education. This condition indicates unresolved inner conflicts, which often lead to destructive behavior. This phenomenon raises fundamental questions about how understanding and internalizing religious values can serve as an internal solution to strengthen students' mental, ethical, and spiritual resilience in facing challenges on campus. This study aims to examine the relationship between religiosity and social behavior of university students located in the Surabaya and Sidoarjo areas. Social behavior in this study covers four main aspects: empathy and social concern, cooperation, tolerance, and responsibility. This study uses the Partial Least Square Structural Equation Modeling (PLS-SEM) method to analyze the paths between constructs through the SMART-PLS application. The results show that religiosity has a significant positive influence on all aspects of social behavior. This finding confirms that the higher the level of religiosity of students, the higher the positive social behavior they exhibit in campus life and society. Thus, properly internalized religious values can serve as a strong foundation for developing caring, tolerant, cooperative, and responsible individuals. These findings are expected to provide a deeper understanding of the role of religion in shaping students' social behavior and serve as a foundation for character development programs in higher education.